2016
DOI: 10.1038/srep37219
|View full text |Cite
|
Sign up to set email alerts
|

Stage-dependent stoichiometric homeostasis and responses of nutrient resorption in Amaranthus mangostanus to nitrogen and phosphorus addition

Abstract: Stoichiometric homeostasis is the ability of plants remaining their element composition relatively stable regardless of changes in nutrient availability, via various physiological mechanisms. Nutrient resorption is one of such key mechanisms, but whether and how nitrogen and phosphorus homeostasis and resorption in plants would change with growth-stages under variable nutrient supply was unclear. A nitrogen (N) and phosphorus (P) fertilizer addition experiment was conducted to evaluate the dynamics of N and P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
(60 reference statements)
0
24
1
Order By: Relevance
“…, Peng et al. ). But, in contrast to those case studies, we also found negative relationships between nutrient remobilization and soil richness for S and base cations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Peng et al. ). But, in contrast to those case studies, we also found negative relationships between nutrient remobilization and soil richness for S and base cations.…”
Section: Discussionmentioning
confidence: 99%
“…, Yuan and Chen , Peng et al. ), and N‐P remobilization efficiency has consequently been used to study nutrient limitation at global scale (Han et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Most nutrient resorption studies focus on terrestrial (upland) evergreen, deciduous, forb and graminoid species (Killingbeck 1996; Aerts and Chapin 1999; Van Heerwaarden et al 2003; Peng et al 2016) with only few studies investigating wetland plant species (Miao 2004; Rejmánková 2005; Rejmánková and Snyder 2008). Rejmánková (2005) observed relatively high nutrient resorption efficiencies for wetland plant species including cattail ( Typha domingensis ) for both N and P across a variety of nutrient limiting conditions.…”
Section: Figurementioning
confidence: 99%
“…Plants with strong sinks (i.e., sites close to developing fruits or new leaf growth) have high resorption, suggesting the roles of source–sink interactions and phloem transport in explaining proportional resorption (Chapin and Moilanen, ; Lambers et al., ). During reproductive growth, flowers and seeds become the largest sink for nutrient resources of annual plants (Yasumura, ; Peng et al., ).…”
mentioning
confidence: 99%
“…The ability to resorb P from senescing leaves was found to be inversely associated with the capacity to downregulate net P uptake (de Campos et al., ; Lambers et al., ). When the nutrient uptake capacity decreases during late growth stages, the remobilized (resorbed) nutrients from senescing organs become the main source to satisfy growth demands (Weiner, ; Peng et al., ). Plant nutrient absorption capacity is closely related to the biomass fraction of roots, or root to shoot ratio (Marschner, ), but the relationship between this ratio and nutrient resorption is unclear.…”
mentioning
confidence: 99%